Climate change impacts and associated economic costs in Ireland - Kelly C. De Bruin; Clement Kweku Kyei; Loïc Henry (The Economic and Social Research Institute (ESRI), 2024)
This paper presents updated and newly derived estimates using various impact models, including biophysical and econometric models, to evaluate the direct economic costs of climate change in Ireland. The estimates are completed for five climate impacts: sea level rise, heat effects on labour productivity, human health, agricultural production, and river flooding. The key findings include (1) Under a moderate warming scenario of SSP2-RCP4.5, with a global mean sea level rise of 0.56 meters, the projected annual cost for the year 2050 would be around exteuro2 billion (2) Rising temperatures and humidity within workplaces can decrease labour productivity (3) The projected changes in climatic conditions are expected to benefit major crops such as barley and wheat moderately, primarily due to the beneficial effects of CO2 fertilisation (4) The projected annual economic damage resulting from river flooding is expected to increase in the future in the absence of additional adaptation measures, and (5) Higher temperatures can contribute to an increase in emergency hospital admissions. It is essential to note that the analyses exclude numerous other impact categories, such as ecosystem services and biodiversity due to the lack of appropriate data. Therefore, these results should be interpreted as a first step to monetise impacts for Ireland, where additional research is needed.
Keywords: 330; Klimawandel; Soziale Kosten; Makroökonometrie; Irland